2014
DOI: 10.1016/j.nbd.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hippocampus in Nav1.6 (Scn8a) mediated seizure resistance

Abstract: SCN1A mutations are the main cause of the epilepsy disorders Dravet syndrome (DS) and genetic epilepsy with febrile seizures plus (GEFS+). Mutations that reduce the activity of the mouse Scn8a gene, in contrast, are found to confer seizure resistance and extend the lifespan of mouse models of DS and GEFS+. To investigate the mechanism by which reduced Scn8a expression confers seizure resistance, we induced interictal-like burst discharges in hippocampal slices of heterozygous Scn8a null mice (Scn8amed/+) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 37 publications
5
51
0
Order By: Relevance
“…These data, together with the observed hippocampal astrocytosis, suggest that forebrain circuits are particularly affected. This conclusion is consistent with the observations of elevated persistent current and early afterdepolarization-like action potentials in hippocampal CA1 and CA3 neurons from these mice (Lopez-Santiago et al, 2015), and with the role of the hippocampus in seizure resistance due to Scn8a haploinsufficiency (Makinson et al, 2014). The lack of transcriptional changes in cerebellum is in agreement with the normal activity of cerebellar Purkinje cells from the D/+ mutant mice (MHM and JLW, unpublished observations).…”
Section: Discussionsupporting
confidence: 90%
“…These data, together with the observed hippocampal astrocytosis, suggest that forebrain circuits are particularly affected. This conclusion is consistent with the observations of elevated persistent current and early afterdepolarization-like action potentials in hippocampal CA1 and CA3 neurons from these mice (Lopez-Santiago et al, 2015), and with the role of the hippocampus in seizure resistance due to Scn8a haploinsufficiency (Makinson et al, 2014). The lack of transcriptional changes in cerebellum is in agreement with the normal activity of cerebellar Purkinje cells from the D/+ mutant mice (MHM and JLW, unpublished observations).…”
Section: Discussionsupporting
confidence: 90%
“…The Scn8a med-jo allele also rescued the premature lethality of Scn1a +/− Dravet syndrome mice and extended the lifespan of Scn1a −/− mutants (45). Reduction of Scn8a expression by conditional deletion of a floxed allele in hippocampal neurons was protective against picrotoxin-induced seizures (46). Together with the present study, these studies demonstrate that increased Na v 1.6 activity can be associated with a predisposition to epilepsy, whereas reduced activity can be protective.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, only rats that previously experienced SE in our study exhibit the increase expression of Nav1.6, and this increase is profoundly seizure intensity-related. Moreover, it has been reported that reduced expression of Nav1.6 and inhibition of Nav1.6 activity can suppress the neuronal hyperexcitability121524. Thus, the increased Nav1.6 expression could be an important molecular alteration in the course of epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%